Corpse Whale - Okpik, Dg Nanouk (Book collections on Project MUSE., 2012)
A self-proclaimed "vessel in which stories are told from time immemorial," poet dg nanouk okpik seamlessly melds both traditional and contemporary narrative, setting her apart from her peers. The result is a collection of poems that are steeped in the perspective of an Inuit of the twenty-first century--a perspective that is fresh, vibrant, and rarely seen in contemporary poetics. Fearless in her craft, okpik brings an experimental, yet poignant, hybrid aesthetic to her first book, making it truly one of a kind. "It takes all of us seeing, hearing, touching, tasting, and smelling to be one," she says, embodying these words in her work. Every sense is amplified as the poems, carefully arranged, pull the reader into their worlds. While each poem stands on its own, they flow together throughout the collection into a single cohesive body. The book quickly sets up its own rhythms, moving the reader through interior and exterior landscapes, dark and light, and other spaces both ecological and spiritual. These narrative, and often visionary, poems let the lives of animal species and the power of natural processes weave into the human psyche, and vice versa. Okpik's descriptive rhythms ground the reader in movement and music that transcend everyday logic and open up our hearts to the richness of meaning available in the interior and exterior worlds.